Double-resin interpenetrating network photo-thermal dual-curing optical fiber bonding fixing glue and preparation method thereof
By employing a dual-resin interpenetrating network photothermal dual-curing technology, the problems of incomplete curing of fiber optic bonding adhesives, inability to cure in shaded areas, and insufficient toughness are solved, achieving a low shrinkage rate and high stability fiber optic bonding and fixing effect, suitable for high-precision and complex optical components.
Patent Information
- Application Number
- CN202511881821.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-15
- Publication Date
- 2026-02-06
AI Technical Summary
Existing fiber bonding and fixing adhesives have problems such as high curing temperature, incomplete reaction, inability to cure in shaded areas, poor toughness, large shrinkage rate, mismatch of thermal expansion coefficients, and insufficient wettability, which lead to short service life and poor reliability of fiber optic devices in complex environments.
By employing a dual-resin interpenetrating network photothermal dual-curing technology, and through the synergistic effect of free radical photoinitiators and cationic photoinitiators, combined with filler regulation, a flexible and rigid resin network is synergistically integrated and grown to form a low-shrinkage optical fiber bonding and fixing adhesive.
It achieves low curing shrinkage, good storage stability, and efficient photothermal dual curing performance, improving the bonding strength and stability of the optical fiber bonding fixation adhesive, making it suitable for high-precision and complex optical components.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of adhesives, in particular to a kind of double resin interpenetrating network optical fiber bonding fixed glue and its preparation method BACKGROUND
[0002] In the field of optical fiber communication and sensing, optical fiber bonding and fixing process is crucial to the long-term stability and reliability of the device. Current market mainstream products rely on imported adhesives, and domestic related industries have not formed a mature technical system. Although imported products dominate the market, they have multiple technical defects: the curing temperature is generally high, which increases the process energy consumption and may damage the optical fiber core; incomplete curing reaction results in insufficient interfacial bonding strength, affecting the service life of the device in complex environments; in the shadow area where ultraviolet light cannot penetrate, effective crosslinking cannot be achieved through pure thermal curing, which severely limits its application in precision optical assemblies; the toughness design of the material is unreasonable, which is prone to brittle fracture when the temperature fluctuates, and at the same time, it applies excessive internal stress to the optical fiber, causing micro-cracks and even the risk of breakage. Although the domestic self-developed alternative products try to solve some of the problems, they generally have a significantly high volume shrinkage rate after curing, which leads to interfacial stress concentration and bonding failure; the thermal expansion coefficient does not match the optical fiber substrate, which is prone to delamination during thermal cycling; the adhesive has poor wettability and is difficult to spread evenly on the surface of the optical fiber, resulting in fluctuations in bonding strength and local defects, which cannot meet the actual needs of high-precision and high-reliability application scenarios. By analyzing the existing curing system in depth, the cationic photocuring mechanism has a slow reaction rate, and bonding failure is prone to occur at the interface between glass and metal substrates, which poses a significant risk of peeling during long-term use; although the free radical photocuring process can be quickly positioned, the surface is prone to residual unreacted monomers, resulting in a tacky state, and the curing shrinkage effect is strong, which may cause cracking of delicate workpieces; the ultraviolet light curing technology cannot trigger a reaction in the shadow area, which is a key bottleneck restricting the assembly of complex structures. The above problems are interwoven, making it difficult for existing adhesives to meet practical requirements in terms of shrinkage control, shadow curing, interfacial stability, and process adaptability, which seriously hinders the improvement of optical fiber device performance and large-scale production. In view of the above problems, the existing technology needs to be improved. SUMMARY
[0003] The present application aims to provide a kind of double resin interpenetrating network optical fiber bonding fixed glue and its preparation method, which has low curing shrinkage rate, good storage stability and efficient photo-thermal dual curing performance, effectively solving the problems of high curing temperature, incomplete reaction, shadow area curing, poor toughness, high shrinkage rate, thermal expansion coefficient mismatch and insufficient wettability in the prior art.
[0004] The application provides a kind of double resin interpenetrating network photo-thermal dual curing optical fiber bonding fixing glue, including the following components by weight ratio: epoxy resin 20-60 parts, acrylate resin 10-30 parts, diluent 5-10 parts, auxiliary agent 0.5-3 parts, cationic photoinitiator 1-10 parts, free radical photoinitiator 1-10 parts, filler 50-80 parts, auxiliary agent includes adhesion promoter and wetting dispersant;Free radical photoinitiator triggers acrylate resin double bond polymerization under ultraviolet light irradiation, realizes positioning curing to form flexible resin network, cationic photoinitiator ultraviolet light irradiation and oven temperature 110 DEG C, curing 1 hour, curing process triggers epoxy group ring opening polymerization of epoxy resin to form rigid resin network, the same amount of cationic photoinitiator and free radical photoinitiator combine filler to control the curing rate of flexible resin network Synergistic rigid resin network jointly interacts and grows curing, form optical fiber bonding fixing glue shrinkage after curing no more than 0.2%, optical fiber bonding fixing glue can be stably stored for a week at 25 DEG C room temperature, viscosity is between 20000-50000 mpa·s.The application provides a kind of double resin interpenetrating network photo-thermal dual curing optical fiber bonding fixing glue, including the following components by weight ratio: epoxy resin 20-60 parts, acrylate resin 10-30 parts, diluent 5-10 parts, auxiliary agent 0.5-3 parts, cationic photoinitiator 1-10 parts, free radical photoinitiator 1-10 parts, filler 50-80 parts, auxiliary agent includes adhesion promoter and wetting dispersant;Free radical photoinitiator triggers acrylate resin double bond polymerization under ultraviolet light irradiation, realizes positioning curing to form flexible resin network, cationic photoinitiator ultraviolet light irradiation and oven temperature 110 DEG C, curing 1 hour, curing process triggers epoxy group ring opening polymerization of epoxy resin to form rigid resin network, the same amount of cationic photoinitiator and free radical photoinitiator combine filler to control the curing rate of flexible resin network Synergistic rigid resin network jointly interacts and grows curing, form optical fiber bonding fixing glue shrinkage after curing no more than 0.2%, optical fiber bonding fixing glue can be stably stored for a week at 25 DEG C room temperature, viscosity is between 20000-50000 mpa·s.The application provides a kind of double resin interpenetrating network photo-thermal dual curing optical fiber bonding fixing glue, including the following components by weight ratio: epoxy resin 20-60 parts, acrylate resin 10-30 parts, diluent 5-10 parts, auxiliary agent 0.5-3 parts, cationic photoinitiator 1-10 parts, free radical photoinitiator 1-10 parts, filler 50-80 parts, auxiliary agent includes adhesion promoter and wetting dispersant;Free radical photoinitiator triggers acrylate resin double bond polymerization under ultraviolet light irradiation, realizes positioning curing to form flexible resin network, cationic photoinitiator ultraviolet light irradiation and oven temperature 110 DEG C, curing 1 hour, curing process triggers epoxy group ring opening polymerization of epoxy resin to form rigid resin network, the same amount of cationic photoinitiator and free radical photoinitiator combine filler to control the curing rate of flexible resin network Synergistic rigid resin network jointly interacts and grows curing, form optical fiber bonding fixing glue shrinkage after curing no more than 0.2%, optical fiber bonding fixing glue can be stably stored for a week at 25 DEG C room temperature, viscosity is between 20000-50000 mpa·s.
[0005] The epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, amino phenol trifunctional epoxy resin, hydrogenated epoxy resin and alicyclic epoxy resin.
[0006] The acrylic resin is any one of polyurethane acrylate, methacrylate and aromatic acrylate resin.
[0007] The diluent is any one or more of benzyl glycidyl ether, butyl glycidyl ether, carbon ten twenty four alkyl glycidyl ether, 1.4-butylene glycol diglycidyl ether, 1.6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether and active diluent such as glycidyl amine.
[0008] The adhesion promoter is any one or more of γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropoxy) propyl trimethoxysilane, γ-methacryloyloxy propyl trimethoxysilane and epoxy silane.
[0009] The wetting dispersant is any one or both of 1-methoxy-2-propanol acetate and 1-methoxy-2-propanol.
[0010] The cationic initiator is one or more of thioonium hexafluoroantimonate, thioonium hexafluorophosphate, and bis(4-dodecylbenzene)iodohexafluoroantimonate.
[0011] The free radical initiator is one or more of 2-isopropylthioxanthonone, 2,4-diethylthioxanthonone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2,4,6-trimethylbenzoyl phosphate ethyl ester, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methylphenylpropane-1-one.
[0012] The filler is one or more of the following: silica powder, aluminum hydroxide, alumina, quartz powder, mica powder, kaolin, and boron nitride.
[0013] A method for preparing a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding and fixing adhesive includes the following steps: Step 1: Preparation of the basic system. 20-60 parts by weight of epoxy resin and 5-10 parts by weight of diluent are dispersed at high speed at room temperature, and stirred at 1200 r / min for 30 minutes. Then, 50-80 parts by weight of filler are added and dispersed, and stirred at 1200 r / min for 30 minutes. Then, 0.5-3 parts by weight of additives are added and dispersed at the same speed for 30 minutes to form an optical fiber bonding and fixing matrix. Step 2: Add functional components. Add 1-10 parts of cationic initiator and 1-10 parts of free radical photoinitiator of the same weight. Disperse and stir at 1000 r / min for 30 minutes to form a uniform and stable finished optical fiber bonding and fixing adhesive.
[0014] This invention employs a synergistic mechanism: free radical initiators (such as 2-hydroxy-2-methylphenylpropane-1-one) achieve rapid localization and curing within 30 seconds, solving the problem of "slow curing"; cationic initiators (such as thioonium hexafluoroantimonate) continuously crosslink under UV+ heating, avoiding the "surface stickiness" of the free radical system (the residual double bonds are completely reacted), while compensating for the deficiency of insufficient UV irradiation in the shaded area (heating can trigger cationic curing).
[0015] Key advantage: The measured shrinkage rate after curing is only 0.118% (density method test: before curing). 1.693 g / cm³ → 1.695 g / cm³ after curing), which is far lower than the conventional shrinkage rate of free radical systems (1%-5%), thus reducing the risk of substrate cracking from the source.
[0016] Formulation design: Employing multi-component synergistic optimization of key performance characteristics
[0017] As can be seen from the above, the optical fiber bonding and fixing adhesive with dual photothermal curing of dual resin interpenetrating network provided in this application and its preparation method achieve synergistic effects (low shrinkage + rapid curing) by selecting initiators (such as the combination of thioonium salts and thioxanthones) and optimizing the curing process (UV + low temperature heating). The combination of dual resins, high fillers, dual initiators and additives achieves comprehensive performance optimization of "low shrinkage rate, matching expansion coefficient, stable bonding strength and aging resistance", which exceeds the expectations of conventional formulation adjustments. Detailed Implementation
[0018] The technical solutions of this application will be clearly and completely described below with reference to the embodiments therein. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. The components of this application described and shown in the embodiments herein can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of this application provided in the embodiments is not intended to limit the scope of the claimed application, but merely represents selected embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0019] Traditional optical fiber bonding adhesives suffer from several drawbacks in application, including excessively high curing temperatures, insufficient curing, inability to achieve pure heat curing in shaded areas, insufficient toughness, and excessive stress on the substrate. Meanwhile, some alternative products exhibit excessive shrinkage, excessive expansion coefficients, and insufficient wettability, failing to meet practical application requirements. Cationic curing systems suffer from slow curing and low bond strength; free radical curing systems exhibit sticky surfaces and excessive shrinkage; and there is a risk of incomplete curing in shaded areas under ultraviolet irradiation.
[0020] To address this issue, this application proposes a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding and fixing adhesive, comprising the following components in the indicated weight proportions: 20-60 parts epoxy resin, 10-30 parts acrylate resin, 5-10 parts diluent, 0.5-3 parts additives, 1-10 parts cationic photoinitiator, 1-10 parts free radical photoinitiator, and 50-80 parts filler. The additives include adhesion promoters and wetting and dispersing agents. The free radical photoinitiator triggers the double bond polymerization of the acrylate resin under ultraviolet irradiation, achieving targeted curing to form a flexible fiber. The resin network is cured by ultraviolet irradiation of the cationic photoinitiator and an oven temperature of 110°C for 1 hour. During the curing process, the epoxy groups of the epoxy resin are triggered to undergo ring-opening polymerization to form a rigid resin network. The cationic photoinitiator and the free radical photoinitiator are used in equal amounts, and the curing rate of the flexible resin network is controlled by the filler. The rigid resin network and the cationic photoinitiator interact and fuse together to grow and cure, forming an optical fiber bonding and fixing adhesive. The shrinkage rate after curing is no more than 0.2%. The optical fiber bonding and fixing adhesive can be stably stored at room temperature of 25°C for one week, and the viscosity is between 20,000 and 50,000 mPa·s.
[0021] For ease of understanding, the following explains some key terms in this embodiment: Interpenetrating polymer network (IPN) photothermal dual curing refers to the polymerization reaction of two different types of resins (epoxy resin and acrylate resin) under the influence of light and heat, forming two interpenetrating and intertwined polymer network structures. Ultraviolet light is used to initiate part of the polymerization reaction, while the oven temperature of 110℃ is used to initiate the other part of the polymerization reaction, thereby achieving complete curing of the adhesive.
[0022] Fiber optic bonding adhesive is a specialized adhesive used to fix or bond optical fibers to specific substrates. This adhesive needs to possess good bond strength, low shrinkage, moderate toughness, and compatibility with both the fiber and the substrate to ensure the stability and reliability of the fiber during long-term use. Flexible resin networks are polymer networks formed by the double-bond polymerization of acrylate resin under the action of a free radical photoinitiator. This network typically possesses a certain degree of elasticity and flexibility, capable of absorbing stress and providing toughness to the cured adhesive layer. Rigid resin networks are polymer networks formed by the ring-opening polymerization of epoxy resin under the action of a cationic photoinitiator. This network typically has high hardness and strength, providing structural support and bond strength to the cured adhesive layer.
[0023] Positioning curing refers to the process of using ultraviolet light to cause the adhesive to undergo a rapid polymerization reaction in a specific area or surface, thereby achieving initial fixation or positioning in a short time, facilitating subsequent operations or deep curing.
[0024] Synergistic interpenetrating growth and curing refers to the interaction and interpenetration of flexible and rigid resin networks during the curing process through their respective polymerization mechanisms, ultimately forming a uniform and stable interpenetrating network structure. This process combines the advantages of both networks, thereby improving the overall performance of the adhesive.
[0025] This embodiment provides a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding adhesive, the components of which include epoxy resin, acrylate resin, diluent, additives, cationic photoinitiator, free radical photoinitiator, and filler. These components are combined in specific weight ratios, wherein the amount of epoxy resin is 20-60 parts, the amount of acrylate resin is 10-30 parts, the amount of diluent is 5-10 parts, the amount of additives is 0.5-3 parts, the amount of cationic photoinitiator is 1-10 parts, the amount of free radical photoinitiator is 1-10 parts, and the amount of filler is 50-80 parts. By precisely controlling the proportions of each component, the adhesive performance can be optimized. The additives include adhesion promoters and wetting and dispersing agents. The adhesion promoters enhance the bonding strength between the adhesive and the optical fiber or substrate; for example, compounds containing silane groups can be selected. The role of wetting and dispersing agents is to improve the uniformity of filler dispersion in the resin system and prevent filler agglomeration. For example, compounds with surface-active functions can be selected.
[0026] Free radical photoinitiators trigger the double bond polymerization of acrylate resins under ultraviolet light irradiation. This polymerization reaction can proceed rapidly, thereby achieving the localized curing of the adhesive and forming a flexible resin network. For example, by setting up an ultraviolet light source to irradiate the area coated with adhesive for a short time, the acrylate resin can be rapidly cross-linked to form a preliminary fixed structure.
[0027] Cationic photoinitiators, under ultraviolet irradiation and an oven temperature of 110°C, trigger the ring-opening polymerization reaction of epoxy groups in epoxy resin after a 1-hour curing process, forming a rigid resin network. For example, after initial positioning and curing, the workpiece is placed in a heated oven for thermosetting at a specific temperature, allowing the epoxy resin system to gradually complete deep cross-linking.
[0028] The amounts of cationic and free radical photoinitiators were set to be the same, and together with fillers, they controlled the curing rate of the flexible resin network, thereby synergistically promoting the interaction and fusion growth and curing of the rigid resin network. For example, by adjusting the type and amount of fillers, the viscosity, light transmittance, and thermal conductivity of the system can be affected, thereby influencing the curing kinetics of the two networks and ensuring that they can interpenetrate and form an interpenetrating network structure during the curing process.
[0029] After curing, the shrinkage rate of the fiber optic bonding adhesive is controlled to be no more than 0.2%. For example, by optimizing the resin system formulation and curing conditions, the stress caused by volume shrinkage during curing can be effectively reduced. Furthermore, the fiber optic bonding adhesive can be stored stably for one week at room temperature (25°C), with its viscosity controlled between 20,000 and 50,000 mPa·s. For example, by selecting appropriate components and adding stabilizers, the shelf life of the adhesive can be extended while ensuring good flowability and workability during application.
[0030] The fiber optic bonding adhesive proposed in this application achieves a combination of rapid positioning curing and deep thermal curing through a dual-resin interpenetrating network photothermal dual curing mechanism. This effectively solves the problems of high curing temperature, uneven curing, and inability to cure in shaded areas associated with traditional adhesives. The adhesive exhibits low shrinkage after curing, reducing stress on the substrate, while also possessing both flexibility and rigidity, thus improving bond strength and stability. Furthermore, the adhesive demonstrates good storage stability and suitable viscosity, facilitating practical applications.
[0031] In some embodiments described above, a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding adhesive is proposed. This adhesive achieves low shrinkage and good storage stability through the synergistic curing of epoxy resin and acrylate resin. However, in practical applications, there are many types of epoxy resins, and different types exhibit significant differences in molecular structure, functionality, and post-curing performance. This can lead to an inability to achieve an optimal balance in the mechanical properties, heat resistance, adhesion to the substrate, and processability of the final cured product, thus affecting the overall performance and applicability of the optical fiber bonding adhesive.
[0032] In this regard, this application further proposes that the epoxy resin in the aforementioned optical fiber bonding and fixing adhesive can be specifically selected from any one of bisphenol A epoxy resin, bisphenol F epoxy resin, aminophenol trifunctional epoxy resin, hydrogenated epoxy resin, or alicyclic epoxy resin. Specifically, when bisphenol A epoxy resin is selected, it has good comprehensive properties, providing excellent mechanical strength, heat resistance, and good adhesion to optical fiber materials for the cured bonding and fixing adhesive, and is one of the most widely used epoxy resins in industry. When bisphenol F epoxy resin is selected, it usually has a lower viscosity, which helps to improve the fluidity and wettability of the adhesive, while the curing speed is relatively fast, which can give the cured product better toughness and chemical corrosion resistance. When aminophenol trifunctional epoxy resin is selected, because its molecular structure contains three epoxy groups, it can form a higher crosslinking density, thereby significantly improving the heat resistance, glass transition temperature, and mechanical properties at high temperatures of the cured adhesive, making it suitable for applications with high heat resistance requirements. When hydrogenated epoxy resins are selected, their saturated molecular structure gives them excellent weather resistance and UV resistance, and they are less prone to yellowing after curing. Their low viscosity also improves workability, making them suitable for applications requiring color stability. When alicyclic epoxy resins are selected, their unique alicyclic structure endows the cured adhesive with excellent UV resistance, electrical insulation, and heat resistance. Furthermore, their curing shrinkage is typically low, which helps to further reduce the curing stress of the fiber optic bonding adhesive and improve the reliability of the bond.
[0033] By optimizing the specific type of epoxy resin described above, the overall performance of the fiber optic bonding adhesive can be precisely controlled according to different application requirements. For example, selecting bisphenol A epoxy resin ensures excellent basic mechanical properties and adhesion; selecting bisphenol F epoxy resin optimizes the flowability and curing speed of the adhesive while improving toughness; selecting aminophenol trifunctional epoxy resin significantly improves the heat resistance and high-temperature mechanical strength of the cured adhesive; while hydrogenated epoxy resin and alicyclic epoxy resin offer unique advantages in weather resistance, anti-yellowing properties, electrical insulation, and reduced curing shrinkage, respectively. This targeted selection allows the interpenetrating network structure formed by epoxy resin and acrylate resin to work more effectively, ensuring that after photothermal dual curing, the bonding adhesive not only maintains low shrinkage and good storage stability but also achieves an optimal balance in terms of mechanical properties, heat resistance, weather resistance, and processability. This significantly improves the reliability and service life of fiber optic bonding, meeting the needs of a wider range of demanding application scenarios.
[0034] This application proposes a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding and fixing adhesive. It utilizes a free radical photoinitiator to trigger the double-bond polymerization of acrylate resin under ultraviolet irradiation, achieving targeted curing to form a flexible resin network. Conversely, a cationic photoinitiator triggers the ring-opening polymerization of epoxy groups in the epoxy resin under ultraviolet irradiation and an oven temperature of 110°C, forming a rigid resin network, thereby achieving the bonding and fixing of the optical fiber. However, in practical applications, there are many types of acrylate resins with significant differences in molecular structure and properties. Inappropriate selection may lead to an imbalance in the cured adhesive's flexibility, adhesion, heat resistance, or mechanical strength, thus affecting the overall performance and long-term stability of the optical fiber bonding and fixing adhesive.
[0035] In this regard, this application further proposes a specific selection of acrylate resin, wherein the acrylate resin can be any one of polyurethane acrylate, methacrylate, or aromatic acrylate resin.
[0036] Polyurethane acrylate is a resin that combines the flexibility, abrasion resistance, and high strength of polyurethane with the rapid curing properties of acrylate. Its molecular chain contains polyurethane segments, which endow the cured product with excellent elasticity and toughness, effectively absorbing stress, improving the buffering and protective ability of the adhesive layer for optical fibers, and enhancing adhesion to various substrates.
[0037] Methacrylates possess high glass transition temperatures and crosslinking densities, and upon curing, they form resin networks with high hardness and excellent chemical resistance. Their rapid curing characteristics contribute to improved production efficiency, while their high mechanical strength and heat resistance enhance the overall structural stability of the colloid.
[0038] Aromatic acrylate resins, due to the presence of aromatic rings in their molecular structure, typically exhibit excellent rigidity, heat resistance, and chemical resistance. Introducing them into optical fiber bonding adhesives can significantly improve the heat distortion temperature and long-term stability of the cured adhesive layer, especially at high temperatures, effectively maintaining the mechanical properties of the colloid.
[0039] The above technical solution addresses the issue of selecting acrylate resins in optical fiber bonding adhesives. This application allows for precise control of the flexible resin network's performance based on specific application requirements by choosing any one of polyurethane acrylate, methacrylate, or aromatic acrylate resins. For example, selecting polyurethane acrylate significantly improves the adhesive's flexibility and impact resistance, effectively mitigating damage to the optical fiber under external stress; selecting methacrylate increases the adhesive's hardness and curing speed, making it suitable for scenarios with high requirements for mechanical strength and production efficiency; while selecting aromatic acrylate resin imparts superior heat resistance and long-term stability to the adhesive. This targeted selection enables the flexible resin network to better synergize with the rigid epoxy resin network, forming a more balanced, lower shrinkage, and superior bonding and fixing effect under various working conditions double interpenetrating network structure. This ensures that the optical fiber bonding adhesive has more reliable mechanical properties and environmental adaptability after curing, effectively improving the protection and fixing effect of the optical fiber.
[0040] To address this issue, this application proposes a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding and fixing adhesive. Its formulation includes a diluent, primarily used to adjust the viscosity of the adhesive to meet specific construction process requirements. However, in practical applications, improper selection of the diluent can lead to poor viscosity stability of the adhesive, affecting its storage life at 25°C, and even causing high shrinkage during curing, thus adversely impacting the bonding and fixing effect and long-term reliability of the optical fiber.
[0041] To address the aforementioned issues, this application further proposes that the diluent be one or more of the following reactive diluents: benzyl glycidyl ether, butyl glycidyl ether, dodecyl tetradecyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and glycidylamine. These reactive diluents refer to diluents whose molecular structure contains functional groups capable of participating in polymerization reactions. Unlike inactive diluents, reactive diluents react with the resin matrix and solidify during the curing process, becoming part of the cured system rather than simply volatilizing or remaining, thus avoiding volume shrinkage and performance degradation caused by diluent volatilization. Their main function is to reduce system viscosity and improve flowability without sacrificing the mechanical properties of the cured product; they can even impart specific properties to the cured product through their structural characteristics.
[0042] Specifically, benzyl glycidyl ether, butyl glycidyl ether, and carbodecyl tetradecyl glycidyl ether are monofunctional glycidyl ether reactive diluents. They have relatively small molecular weights and excellent dilution effects, effectively reducing the initial viscosity of optical fiber bonding adhesives to within the range of 20,000-50,000 mPa·s, facilitating coating and handling. Simultaneously, their epoxy groups can participate in the ring-opening polymerization reaction of epoxy resins, becoming part of the rigid resin network, which helps reduce curing shrinkage. 1,4-Butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and neopentyl glycol diglycidyl ether are difunctional glycidyl ether reactive diluents. They contain two epoxy groups, which, while reducing viscosity, can increase the crosslinking density of the cured network, thereby enhancing the mechanical strength, heat resistance, and chemical stability of the cured product. Due to the presence of flexible segments in their molecular chains, they can also impart a certain degree of toughness to the cured product, helping to alleviate curing stress and further reduce shrinkage. In addition to epoxy groups, glycidyl amine reactive diluents also contain amine groups. The amine groups can act as accelerators or curing agents for epoxy resin curing, accelerating the ring-opening polymerization reaction and improving curing efficiency. Simultaneously, their epoxy groups can also participate in polymerization, forming a denser network structure.
[0043] By selecting the aforementioned reactive diluents, the problems of poor viscosity stability and high curing shrinkage caused by improper diluent selection can be effectively solved. Specifically, these reactive diluents, while reducing the initial viscosity of the fiber optic bonding adhesive, contain functional groups in their molecular structure that can participate in polymerization reactions. During the photothermal dual curing process, they undergo copolymerization reactions with epoxy resin and / or acrylate resin, becoming part of the cured network. This not only avoids the volume shrinkage caused by the volatilization of traditional inactive diluents, but also improves the density and uniformity of the cured network through their participation in crosslinking, thereby significantly reducing the post-curing shrinkage rate and ensuring it is no greater than 0.2%. In addition, the introduction of reactive diluents helps maintain the viscosity stability of the adhesive at room temperature (25°C), extends the shelf life, and ensures the reliability and operability of the fiber optic bonding adhesive in practical applications.
[0044] This application proposes a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding adhesive. This adhesive forms a flexible and rigid resin network through a photothermal dual-curing mechanism, aiming to provide stable bonding and fixation for optical fibers. However, in practical applications, the optical fiber bonding adhesive needs to achieve reliable bonding with various substrates (such as optical fibers, connector materials, etc.). If the adhesion between the adhesive and the substrate is insufficient, problems such as debonding and cracking of the cured adhesive layer may occur during use, thereby affecting the long-term stability and reliability of the optical fiber connection.
[0045] In this regard, this application further proposes to include an adhesion promoter in the optical fiber bonding and fixing adhesive, wherein the adhesion promoter is one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and epoxysilane.
[0046] Adhesion promoters are chemical substances that can significantly improve the bond strength between adhesives and the surfaces of adherends. Their mechanism of action typically involves forming chemical bonds or a physical adsorption layer at the adhesive-substrate interface, thereby enhancing interfacial adhesion, improving adhesive wettability, and increasing the adhesive's ability to impregnate the substrate.
[0047] Specifically, γ-aminopropyltriethoxysilane is an aminosilane coupling agent containing amino and alkoxysilyl groups in its molecular structure. The amino group can react with functional groups in epoxy or acrylate resins, while the alkoxysilyl group, after hydrolysis, can form silanols with hydroxyl groups on the substrate surface, thereby forming covalent or hydrogen bonds with the substrate surface. This establishes a "molecular bridge" between the organic polymer and the inorganic substrate, significantly improving adhesion strength. γ-(2,3-epoxypropoxy)propyltrimethoxysilane is an epoxysilane coupling agent containing epoxy and alkoxysilyl groups in its molecule. The epoxy group can react with epoxy groups or curing agents in epoxy resin systems, while the alkoxysilyl group, similarly, can form silanols with the substrate surface after hydrolysis, thereby forming strong chemical bonds with the substrate surface and effectively enhancing the adhesion between the adhesive and the substrate. γ-Methacryloxypropyltrimethoxysilane is a methacryloyloxysilane coupling agent containing polymerizable methacryloyloxy and alkoxysilane groups in its molecule. The methacryloyloxy group can participate in the free radical polymerization of acrylate resins, while the alkoxysilane group forms bonds with the substrate surface through hydrolysis, thereby establishing an effective connection between the organic phase of the adhesive and the inorganic phase of the substrate, improving adhesion. Epoxysilanes are a class of compounds containing epoxy and silane functional groups. The epoxy group can react with components in the epoxy resin system, while the silane group can react with hydroxyl groups on the surface of inorganic substrates (such as glass, metal oxides, etc.) to form stable chemical bonds. These coupling agents, through their dual reactivity, form a strong interfacial layer between the organic polymer and the inorganic substrate, thereby significantly improving the adhesion, water resistance, and heat resistance of the adhesive.
[0048] By introducing the aforementioned adhesion promoters into the optical fiber bonding adhesive, these promoters can act as molecular bridges, establishing strong chemical bonds between the organic polymer components of the adhesive (such as epoxy resin and acrylate resin) and the surface of inorganic substrates such as optical fibers or connectors. Specifically, one functional group of these silane coupling agents can react or copolymerize with the resin system, while the silane group at the other end hydrolyzes to form stable silanol bonds with the hydroxyl groups on the substrate surface. This bidirectional chemical bonding mechanism greatly enhances the bonding strength between the adhesive and the substrate interface, effectively solving the problem of adhesive debonding that may occur after curing. Therefore, this optical fiber bonding adhesive can achieve more reliable and durable bonding and fixation of optical fibers, significantly improving the mechanical strength, environmental stability, and long-term reliability of the optical fiber connection, avoiding connection failure due to insufficient adhesion, and thus ensuring the stability of optical signal transmission.
[0049] In the preparation of photothermal dual-curing fiber optic bonding adhesives using a dual-resin interpenetrating network (IPN), multiple components are typically introduced to achieve excellent bonding performance and low shrinkage after curing. These components include epoxy resin, acrylate resin, diluents, additives, photoinitiators, and a large amount of filler. However, uniformly dispersing these components, especially a high proportion of filler, into the resin matrix often presents challenges. Uneven filler dispersion can easily lead to system instability, resulting in sedimentation, agglomeration, and other phenomena. This, in turn, affects the storage stability, curing rate, and mechanical properties and shrinkage rate of the cured fiber optic bonding adhesive, making it difficult to ensure the consistency of the final product's performance.
[0050] In this regard, this application further proposes that the wetting and dispersing agent in the additive is one or both of 1-methoxy-2-propanol acetate and 1-methoxy-2-propanol. Wetting and dispersing agents play a crucial role in optical fiber bonding and fixing adhesives. Their main functions are to reduce the surface tension of the system, promote the wetting of filler particles, and prevent the filler particles from re-aggregating in the resin matrix, thereby ensuring the uniform dispersion of each component and the long-term stability of the system. 1-Methoxy-2-propanol acetate is a commonly used solvent and dispersant with good solubility and a moderate evaporation rate. As a wetting and dispersing agent, it can effectively reduce the interfacial tension between the resin and the filler, allowing the filler particle surface to be fully wetted, thus making it easier to disperse in the resin system. Its ester and ether groups in its molecular structure give it good compatibility with various resins and fillers, contributing to the formation of a stable dispersion system. 1-Methoxy-2-propanol is also a high-performance solvent and dispersant with low toxicity and good environmental friendliness. It can serve as a carrier for coupling agents or dispersants, helping them to better adsorb onto the filler surface, or directly as a dispersant, preventing the attraction and aggregation of filler particles through steric hindrance or electrostatic repulsion. Its moderate polarity allows it to effectively wet inorganic fillers and maintain good miscibility with organic resin systems. In practical applications, depending on the specific formulation and the properties of the filler, 1-methoxy-2-propanol acetate or 1-methoxy-2-propanol can be used alone, or the two can be mixed in an appropriate ratio to achieve the best wetting and dispersion effect.
[0051] By selecting one or both of 1-methoxy-2-propanol acetate and 1-methoxy-2-propanol as wetting and dispersing agents, the dispersion state of fillers in optical fiber bonding adhesives can be significantly improved. These specific wetting and dispersing agents can effectively reduce the interfacial tension between the filler and the resin matrix, promote the full wetting of filler particles, and provide stable steric hindrance or electrostatic repulsion, thereby inhibiting the agglomeration and sedimentation of filler particles. This uniform and stable dispersion ensures the viscosity stability of the optical fiber bonding adhesive during storage and avoids performance inconsistencies caused by filler sedimentation. More importantly, during the curing process, the uniformly dispersed filler can more effectively synergistically promote the interaction and fusion growth of the flexible and rigid resin networks, resulting in a denser and more uniform internal structure of the cured adhesive layer. This effectively controls the curing shrinkage rate to no more than 0.2%, and ensures the mechanical properties and long-term reliability of the final product.
[0052] In some embodiments described above, a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding adhesive is proposed. This adhesive utilizes a cationic photoinitiator to trigger the ring-opening polymerization of epoxy resin under ultraviolet irradiation and thermal curing conditions, forming a rigid resin network. This network synergizes with a flexible resin network triggered by a free radical photoinitiator to achieve low shrinkage and good storage stability. However, in practical applications, the selection of the cationic photoinitiator has a crucial impact on curing efficiency, curing depth, the mechanical properties of the final cured product, and the storage stability of the system. An inappropriate selection may lead to incomplete curing, mismatched curing speeds, or premature polymerization during storage, thereby affecting the overall performance of the optical fiber bonding adhesive.
[0053] In this regard, this application further proposes that the above-mentioned cationic initiator is one or more of thioonium hexafluoroantimonate, thioonium hexafluorophosphate, and bis(4-dodecylbenzene)iodohexafluoroantimonate.
[0054] Specifically, thioonium hexafluoroantimonate, as a highly efficient cationic photoinitiator, can rapidly decompose under ultraviolet irradiation to produce strong Lewis acids or Brønsted acids. These acids can effectively initiate the ring-opening polymerization reaction of epoxy resins. Its characteristics include high photoinitiation efficiency and good thermal stability, continuously providing active species during ultraviolet light and subsequent thermal curing, ensuring full curing of the epoxy resin, and contributing to the formation of a dense, rigid resin network. Thionium hexafluorophosphate, also an important cationic photoinitiator, can efficiently generate acidic substances under ultraviolet light, thereby initiating the polymerization of epoxy resins. Compared to hexafluoroantimonate, hexafluorophosphate may exhibit different reactivity and storage stability in some systems, but it remains an effective choice for achieving cationic photocuring of epoxy resins, ensuring a smooth curing process and positively impacting the properties of the final cured product. Bis(4-dodecylbenzene)iodohexafluoroantimonate is an iodonium salt-based cationic photoinitiator with specific substituents. The dodecylphenyl group imparts excellent oil solubility and compatibility with the resin system to this initiator, facilitating its uniform dispersion in the adhesive and thus improving photoinitiation efficiency. Simultaneously, hexafluoroantimonate, as a counterion, ensures its ability to generate strong acid under light irradiation, effectively initiating the ring-opening polymerization of epoxy resin. Its structural characteristics enable it to provide superior storage stability or faster curing speed in certain formulations, facilitating precise control of the curing process and ultimately forming a high-performance interpenetrating network structure.
[0055] By selecting one or more of thioonium hexafluoroantimonate, thioonium hexafluorophosphate, and bis(4-dodecylbenzene)iodohexafluoroantimonate as cationic photoinitiators, this application effectively solves the problems of insufficient curing efficiency, uneven curing, or poor storage stability caused by improper selection of cationic photoinitiators in the prior art. These specific cationic photoinitiators have high photoinitiation efficiency and good thermal stability, ensuring that under ultraviolet irradiation and subsequent oven curing at 110°C for 1 hour, the epoxy groups of the epoxy resin can fully and efficiently undergo ring-opening polymerization to form a dense and high-performance rigid resin network. At the same time, these initiators, together with the free radical photoinitiators and fillers in the system, can precisely control the curing rate of the flexible resin network, allowing it to interact and fuse with the rigid resin network for growth and curing, thereby forming an optical fiber bonding and fixing adhesive with uniform structure, low internal stress, and a post-curing shrinkage rate of no more than 0.2%. In addition, these preferred cationic photoinitiators can also improve the storage stability of the optical fiber bonding adhesive at room temperature of 25°C, ensuring that it can be stored stably for one week and maintain a viscosity between 20,000 and 50,000 mPa·s, thereby ensuring the reliability and consistency of the product in practical applications.
[0056] In some embodiments described above, a flexible resin network is formed by triggering the double bond polymerization of acrylate resin under ultraviolet light irradiation using a free radical photoinitiator. However, in practical applications, if the activity or light absorption characteristics of the free radical photoinitiator are poor, the polymerization reaction of the acrylate resin may be incomplete or the curing speed may be too slow, thereby affecting the formation quality and efficiency of the flexible resin network. This, in turn, negatively impacts the final curing shrinkage rate, mechanical properties, and synergistic curing effect with the rigid resin network of the optical fiber bonding adhesive.
[0057] In this regard, this application further proposes that the free radical initiator is one or more of 2-isopropylthioxanthonone, 2,4-diethylthioxanthonone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2,4,6-trimethylbenzoyl phosphate ethyl ester, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methylphenylpropane-1-one.
[0058] Specifically, the selected free radical initiators cover a variety of highly efficient types. For example, 2-isopropylthioxanthones and 2,4-diethylthioxanthones belong to the thioxanthones class of photoinitiators. They typically have a wide light absorption range, especially strong absorption in the long-wave ultraviolet region, which can effectively initiate polymerization. They often work synergistically with amine auxiliaries to improve initiation efficiency and curing depth, making them suitable for applications requiring deeper curing.
[0059] For example, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide and 2,4,6-trimethylbenzoyl phosphate belong to the acylphosphine oxide class of photoinitiators. These initiators are characterized by high activity, low yellowing, and strong deep curing ability, making them particularly suitable for systems with high requirements for curing depth and color. Under ultraviolet light, they generate free radicals through an efficient α-cleavage mechanism, which can rapidly initiate the polymerization of acrylate resins.
[0060] Furthermore, 1-hydroxycyclohexylphenyl ketone and 2-hydroxy-2-methylphenylpropane-1-one belong to the α-hydroxyketone class of photoinitiators. These initiators have high photoinitiation efficiency, and the products are colorless and transparent, making them suitable for applications with strict requirements for transparency and color stability. They also generate free radicals through an α-cleavage mechanism, ensuring rapid polymerization.
[0061] By employing the above technical solutions, selecting one or more of the following as free radical photoinitiators—2-isopropylthioxanthonone, 2,4-diethylthioxanthonone, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, 2,4,6-trimethylbenzoyl phosphate, 1-hydroxycyclohexylphenyl ketone, and 2-hydroxy-2-methylphenylpropane-1-one—can significantly improve the polymerization efficiency and curing speed of acrylate resins under ultraviolet irradiation. These specific free radical photoinitiators possess excellent light absorption characteristics and highly efficient free radical generation activity, ensuring that the flexible resin network can be formed rapidly, uniformly, and fully during the positioning and curing stage. The formation of this highly efficient and high-quality flexible network provides a solid foundation for the subsequent thermal curing of epoxy resin. It helps to precisely control the curing shrinkage rate of the fiber bonding adhesive, ensuring it is no more than 0.2%, and guarantees the good matching between the flexible resin network and the rigid resin network during the synergistic interaction and fusion growth and curing process. This improves the overall mechanical properties, bonding strength and long-term stability of the cured adhesive, while maintaining excellent storage stability at 25°C for one week.
[0062] In some of the above embodiments, a dual-resin interpenetrating network photothermal dual-curing optical fiber bonding adhesive was proposed, which contains a certain amount of filler. However, relying solely on the amount of filler added to control the curing shrinkage rate, mechanical strength, thermal stability, and compatibility with the optical fiber of the adhesive may have limitations. If the filler is not selected properly, the cured adhesive may have an excessively high shrinkage rate, generating internal stress, which in turn affects the long-term reliability of the optical fiber and the bonding and fixing effect.
[0063] In this application, the filler is further specified as one or more of the following: silica powder, aluminum hydroxide, alumina, quartz powder, mica powder, kaolin, and boron nitride. Specifically, silica powder has a low coefficient of thermal expansion and good insulation properties, which can effectively reduce the curing shrinkage rate of the colloid, reduce the internal stress generated during curing, and improve the dimensional stability of the colloid. Aluminum hydroxide, as an inorganic filler, can not only improve the flame retardant properties of the colloid, but also improve its thermal conductivity to a certain extent, which helps to ensure uniform heat distribution during curing, thereby further optimizing the curing effect. Alumina has high hardness, high strength, and excellent wear resistance, which can significantly improve the mechanical properties of the cured colloid and enhance its impact and scratch resistance. At the same time, its good thermal conductivity also helps to dissipate heat. Quartz powder, similar to silica powder, has a low coefficient of thermal expansion and good chemical stability, which can effectively control the shrinkage of the colloid and improve its weather resistance and mechanical strength, ensuring the long-term stability of optical fiber bonding. Mica powder, with its lamellar structure, imparts a good layered structure to the colloid, improving its barrier properties and dimensional stability, reducing moisture and gas permeation, and thus extending the service life of the optical fiber bonding adhesive. Kaolin is an economical filler that improves the rheological and thixotropic properties of the colloid, facilitating application. It also enhances the mechanical strength and hardness of the colloid to some extent. Boron nitride possesses extremely high thermal conductivity and excellent electrical insulation, making it particularly suitable for applications requiring efficient heat dissipation. In optical fiber bonding adhesives, boron nitride effectively dissipates the heat generated during optical fiber operation, preventing localized overheating and thus improving the reliability of the optical fiber.
[0064] Through the above technical solution, in the optical fiber bonding and fixing adhesive with dual-resin interpenetrating network photothermal dual curing, by selecting one or more of silica powder, aluminum hydroxide, alumina, quartz powder, mica powder, kaolin, and boron nitride as fillers, the physicochemical properties of the adhesive can be precisely controlled according to specific application requirements. For example, the introduction of silica powder and quartz powder can significantly reduce the curing shrinkage rate of the adhesive, effectively controlling the post-curing shrinkage rate to no more than 0.2%, thereby minimizing stress on the optical fiber and avoiding performance degradation. Alumina and mica powder can enhance the mechanical strength and dimensional stability of the adhesive, improving its impact resistance and wear resistance. The addition of aluminum hydroxide and boron nitride can respectively improve the flame retardancy and thermal conductivity of the adhesive, ensuring the safety and reliability of the optical fiber under different working environments. The synergistic effect of these specific fillers enables the flexible and rigid resin networks to better control internal stress during the interactive fusion growth and curing process, forming a more stable and superior interpenetrating network. This ensures that the fiber bonding and fixing adhesive can be stably stored at room temperature of 25°C for one week and maintain a suitable viscosity of 20,000-50,000 mPa·s, ultimately achieving reliable and long-term bonding and fixing of the optical fiber.
[0065] In the preparation of photothermal dual-curing optical fiber bonding and fixing adhesives with dual resin interpenetrating networks, the mixing uniformity and dispersion stability of each component are crucial to the performance of the final product. Insufficient mixing or uneven dispersion of components may lead to incomplete curing, large performance fluctuations, and even affect the storage stability and post-curing shrinkage of the adhesive.
[0066] In response, this application further proposes a method for preparing a fiber optic bonding and fixing adhesive that undergoes photothermal dual curing using a dual-resin interpenetrating network, comprising the following steps: Step 1: Preparation of the basic system. 20-60 parts by weight of epoxy resin and 5-10 parts by weight of diluent are dispersed at high speed at room temperature, stirring at 1200 rpm for 30 minutes. Then, 50-80 parts by weight of filler are added and dispersed, stirring at 1200 rpm for 30 minutes. Finally, 0.5-3 parts by weight of additives are added and dispersed at the same rate for 30 minutes to form the optical fiber bonding and fixing matrix.
[0067] In this process, the epoxy resin and diluent are dispersed at high speed at room temperature and stirred at 1200 rpm for 30 minutes to ensure that the two liquid components are thoroughly and uniformly mixed. Epoxy resin typically has a high viscosity, and the addition of diluent can effectively reduce the overall viscosity of the system. High-speed dispersion provides sufficient shear force to ensure that a homogeneous state is reached within the specified time, laying a good dispersion foundation for the subsequent addition of solid components.
[0068] Subsequently, add 50-80 parts of filler and disperse by stirring at 1200 rpm for 30 minutes. The addition of filler is crucial for controlling the shrinkage, mechanical properties, and viscosity of the colloid. Since fillers are usually solid powders, their uniform dispersion in the resin system directly affects the performance of the final product. Continuing dispersion at the same speed after the epoxy resin and diluent are uniformly mixed ensures that the filler particles are fully wetted, deagglomerated, and uniformly distributed in the resin matrix, avoiding agglomeration and thus ensuring the consistency of the macroscopic properties of the colloid.
[0069] Next, add 0.5-3 parts of additives and disperse and stir at this rate for 30 minutes to form the optical fiber bonding and fixing matrix. Additives, including adhesion promoters and wetting and dispersing agents, play a crucial role in the colloid. Adhesion promoters enhance the bonding strength between the colloid and substrates such as optical fibers, while wetting and dispersing agents help stabilize the dispersion of fillers in the resin system. Adding additives after the base system and fillers are uniformly dispersed and continuing dispersion ensures that these functional components are evenly distributed throughout the colloidal matrix, fully exerting their functions and forming a stable optical fiber bonding and fixing matrix.
[0070] Step 2: Addition of functional components. Add 1-10 parts of cationic initiator and 1-10 parts of free radical photoinitiator of the same weight, and disperse and stir at 1000 r / min for 30 minutes to form a uniform and stable finished optical fiber bonding and fixing adhesive.
[0071] Cationic initiators and free radical photoinitiators are the core components for achieving dual photothermal curing. They are photosensitive and require careful attention to avoid premature initiation. Therefore, after thorough dispersion of the base system, fillers, and additives, the initiator is added and dispersed for 30 minutes at a low rotation speed (1000 r / min) to ensure uniform distribution and prevent premature decomposition or reduced activity due to excessive shear force or localized overheating. This gentle yet thorough mixing method ensures the activity and uniformity of the initiator throughout the colloid, thereby guaranteeing the efficiency and consistency of the subsequent photothermal curing process, ultimately forming a uniform and stable finished fiber optic bonding and fixing adhesive.
[0072] The above preparation method first involves high-speed dispersion of epoxy resin and diluent, effectively reducing the system viscosity and creating a favorable dispersion environment for the subsequent addition of solid components. Fillers and additives are then added in batches while continuous high-speed dispersion ensures that these solid and functional components are fully wetted, depolymerized, and uniformly distributed within the resin matrix, preventing agglomeration and stratification, thus forming a highly uniform and stable optical fiber bonding and fixing adhesive matrix. Finally, a photoinitiator is added and dispersed under relatively mild conditions, ensuring uniform distribution of the initiator while effectively preventing activity loss or premature initiation. This step-by-step, high-speed refined preparation process significantly improves the dispersion uniformity and stability of each component in the colloid, ensuring the stability of the finished optical fiber bonding and fixing adhesive during storage, as well as its excellent performance with a post-curing shrinkage rate of no more than 0.2%, and guaranteeing the efficiency of the photothermal dual curing process and the consistency of the final cured product's performance.
[0073] The following example will provide a more detailed explanation of the above technical solution: In the manufacturing process of optical communication devices, it is necessary to precisely bond and fix fiber arrays to a substrate. Existing technologies often face problems such as excessively high curing temperatures, incomplete curing, failure to cure in shaded areas, insufficient adhesive layer toughness, and excessive stress on the substrate. Furthermore, some alternative products suffer from defects such as excessive shrinkage, excessive coefficient of thermal expansion, and insufficient wettability. To address these technical challenges, this example provides a dual-resin interpenetrating network photothermal dual-curing fiber bonding adhesive.
[0074] First, the optical fiber bonding and fixing adhesive is prepared according to the following proportions: 40 parts epoxy resin (e.g., bisphenol A epoxy resin), 20 parts acrylate resin (e.g., polyurethane acrylate), 7 parts diluent (e.g., 1,4-butanediol diglycidyl ether), 1.5 parts additives, 5 parts cationic photoinitiator (e.g., thionyl hexafluoroantimonate), 5 parts free radical photoinitiator (e.g., (2,4,6-trimethylbenzoyl)diphenylphosphine oxide), and 65 parts filler (e.g., silica powder). The additives include an adhesion promoter (e.g., γ-(2,3-epoxypropoxy)propyltrimethoxysilane) and a wetting and dispersing agent (e.g., 1-methoxy-2-propanol).
[0075] The preparation process consists of two steps: Step 1: Preparation of the basic system. 40 parts of bisphenol A epoxy resin and 7 parts of 1,4-butanediol diglycidyl ether were dispersed and stirred at 1200 rpm for 30 minutes at room temperature. Then, 65 parts of silica powder were added, and stirring continued at 1200 rpm for 30 minutes. Next, 1.5 parts of additives (including γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 1-methoxy-2-propanol) were added, and the mixture was dispersed and stirred at the same rate for 30 minutes to form the optical fiber bonding and fixing matrix.
[0076] Step 2: Addition of functional components. Add 5 parts of thioonium hexafluoroantimonate and 5 parts of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide to the above matrix, and disperse and stir at 1000 rpm for 30 minutes to form a homogeneous and stable finished optical fiber bonding and fixing adhesive. This adhesive can be stored stably at room temperature (25°C) for one week, with a viscosity controlled between 20,000 and 50,000 mPa·s, facilitating subsequent coating operations.
[0077] In practical applications, User A applies the prepared optical fiber bonding adhesive to the substrate and then precisely places the optical fiber array in the adhesive layer.
[0078] First, positioning and curing are performed: the fiber array coated with adhesive is irradiated with ultraviolet light. During this process, a free radical photoinitiator (e.g., (2,4,6-trimethylbenzoyl)diphenylphosphine oxide) rapidly triggers the double-bond polymerization of the acrylate resin (e.g., polyurethane acrylate) under ultraviolet light. This process quickly forms a flexible resin network, providing immediate positioning and initial fixation for the optical fiber. Compared to the slow curing of traditional pure cationic curing systems, this step significantly improves the curing speed, avoids the surface stickiness common in free radical curing systems, and effectively reduces initial shrinkage, thus minimizing stress on the optical fiber and substrate.
[0079] The final curing process then proceeds: the pre-cured components are placed in an oven and cured at 110°C for 1 hour, while continuing UV irradiation. During this stage, the cationic photoinitiator (e.g., thioonium hexafluoroantimonate) is triggered by the combined effects of UV light and heat, initiating the ring-opening polymerization of the epoxy groups in the epoxy resin (e.g., bisphenol A epoxy resin) to form a rigid resin network. This dual photothermal curing mechanism ensures that the adhesive layer is fully cured even in shadow areas inaccessible to UV light, solving the blind zone problem inherent in pure UV curing and overcoming the deficiency of insufficient curing in existing products.
[0080] In this curing process, the amounts of cationic photoinitiator and free radical photoinitiator are equal. Combined with the synergistic effect of fillers (e.g., silica powder), the curing rate of the flexible resin network is precisely controlled, allowing it to interact and fuse with the rigid resin network for growth. This synergistic curing forms a unique interpenetrating dual-resin network structure, resulting in a curing fiber bonding adhesive shrinkage rate of no more than 0.2%. This is significantly superior to existing products with excessively high shrinkage rates, which easily lead to workpiece tearing. The flexible resin network imparts good toughness to the adhesive layer, effectively alleviating stress on the substrate and compensating for the lack of toughness in traditional epoxy adhesives. The rigid resin network provides excellent bonding strength and structural stability, solving the problems of low bonding strength and failure risk in bonding glass and metal substrates in cationic curing systems. Furthermore, adhesion promoters (e.g., γ-(2,3-epoxypropoxy)propyltrimethoxysilane) further enhance the bonding performance between the adhesive layer and the optical fiber and substrate, while wetting and dispersing agents (e.g., 1-methoxy-2-propanol) ensure good wettability of the adhesive solution to the substrate, solving the problem of insufficient wettability in existing products.
[0081] Through the aforementioned photothermal dual curing process, the optical fiber bonding and fixing adhesive achieves comprehensive performance including rapid positioning, thorough curing, low shrinkage, high toughness, and high bonding strength. It effectively solves various technical problems existing in the prior art and provides a reliable solution for optical fiber bonding and fixing.
[0082] Example Formula 1:
[0083] Applicable scenarios: Fiber optic bonding and fixing. Key performance indicators: Viscosity = 35000 mPa·s; Coefficient of thermal expansion = 20 ppm / ℃; The product density before and after curing was tested using the density method to obtain the shrinkage rate, and the data are as follows: ① Data before curing, measured using a liquid density meter: 1.693 g / cm³ ②The cured density, tested using the impregnation method, is 1.695 g / cm³. ③ The calculated shrinkage rate is: 0.118% Tensile shear strength (glass-ABS, UV + heat curing) = 14.8 MPa, stable at room temperature (25℃) for one week without delamination.
[0084] Example Formula 2: High-toughness type (suitable for vibration environments, such as automotive fiber optic assemblies)
[0085] Application scenarios: Fiber optic bonding and fixing. Key performance indicators: Viscosity = 32000 mPa·s; Coefficient of thermal expansion = 22 ppm / ℃; Shrinkage rate = 0.11%; Tensile shear strength (glass-ABS, UV + heat curing) = 15.0 MPa, after 300 hours of dual 85 aging = 14.8 MPa (retention rate = 99%); Impact strength = 18 kJ / m² (30% better than conventional formulations); Stable at room temperature (25℃) for one week without delamination.
[0086] Formula 3:
[0087] Application Scenarios: Fiber optic bonding and fixing. Key Performance: Viscosity = 48000 mPa·s; Coefficient of thermal expansion = 14 ppm / ℃ (low expansion characteristics); Shrinkage = 0.13%; Tensile shear strength (glass-ABS, UV + heat curing) = 14.5 MPa, after 300 hours of double 85 aging = 14.2 MPa (retention rate = 98%); High temperature resistance: Strength retention rate = 95% after 24 hours of constant temperature at 150℃; Stable storage at room temperature at 25℃ for one week without delamination.
[0088] Formula 4: Low viscosity type (suitable for fine gap filling and small-sized fiber optic assemblies)
[0089] Applicable Scenarios: Fiber optic bonding and fixing. Key Performance Predictions: Viscosity = 22000 mPa·s (low viscosity, excellent flowability); Coefficient of Thermal Expansion = 25 ppm / ℃; Shrinkage = 0.10% (low shrinkage, avoiding gap residue); Tensile Shear Strength (glass-ABS, UV + heat curing) = 14.2 MPa, after 300 hours of dual 85 aging = 13.9 MPa (retention rate = 8%); Penetration Capability: Can quickly penetrate and fill gaps of 0.05 mm; Stable at room temperature (25℃) for one week without delamination.
[0090] Formula 5:
[0091] Applicable scenarios: Fiber optic bonding and fixing. Key performance predictions: Viscosity = 42000 mPa·s; Coefficient of thermal expansion = 18 ppm / ℃; Shrinkage rate = 0.12%; Tensile shear strength (glass-ABS, UV + heat curing) = 15.5 MPa, after 300 hours of dual 85 aging = 15.3 MPa (retention rate = 99%); Stable at room temperature (25℃) for one week without delamination.
[0092] The above description is merely an embodiment of this application and is not intended to limit the scope of protection of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A dual-resin interpenetrating network photo-thermal dual-cured optical fiber bonding and securing adhesive, characterized by: The optical fiber bonding fixing glue comprises the following components in parts by weight: 20-60 parts of epoxy resin, 10-30 parts of acrylate resin, 5-10 parts of diluent, 0.5-3 parts of additive, 1-10 parts of cationic photoinitiator, 1-10 parts of free radical photoinitiator and 50-80 parts of filler, wherein the additive comprises adhesion promoter and wetting dispersant; the free radical photoinitiator triggers the polymerization of the double bond of the acrylate resin under ultraviolet irradiation to realize positioning curing to form a flexible resin network; the cationic photoinitiator is ultraviolet irradiated and cured at an oven temperature of 110 DEG C for 1 hour, and the curing process triggers the ring-opening polymerization of the epoxy group of the epoxy resin to form a rigid resin network; the cationic photoinitiator and the free radical photoinitiator are used in the same amount, and the filler controls the curing rate of the flexible resin network to synergistically grow and cure the rigid resin network to form the optical fiber bonding fixing glue, and the shrinkage rate of the optical fiber bonding fixing glue after curing is not greater than 0.2%; the optical fiber bonding fixing glue can be stably stored for one week at room temperature of 25 DEG C, and the viscosity is between 20,000-50,000 mPa·s.
2. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The epoxy resin is any one of bisphenol A epoxy resin, bisphenol F epoxy resin, amino phenol trifunctional epoxy resin, hydrogenated epoxy resin and alicyclic epoxy resin.
3. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding adhesive and the preparation method thereof according to claim 1, characterized in that: The acrylate resin is any one of polyurethane acrylate, methacrylate and aromatic acrylate resin.
4. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The diluent is any one or more of benzyl glycidyl ether, butyl glycidyl ether, carbon ten twenty four alkyl glycidyl ether, 1.4-butylene glycol diglycidyl ether, 1.6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether and active diluent such as glycidyl amine.
5. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The adhesion promoter is any one or more of gamma-aminopropyl triethoxysilane, gamma-(2,3-epoxypropoxy) propyl trimethoxysilane, gamma-methacryloyloxy propyl trimethoxysilane and epoxy silane.
6. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The wetting dispersant is any one or both of 1-methoxy-2-propanol acetate and 1-methoxy-2-propanol.
7. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The cationic initiator is any one or more of sulfonium hexafluoroantimonate, sulfonium hexafluorophosphate and bis(4-dodecylbenzene) iodine hexafluoroantimonate.
8. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The free radical initiator is any one or more of 2-isopropyl thioxanthone, 2,4-diethyl thioxanthone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, 2,4,6-trimethyl benzoyl ethyl phosphate, 1-hydroxy cyclohexyl phenyl ketone and 2-hydroxy-2-methyl phenyl propane-1-ketone.
9. The dual-resin interpenetrating network photo-thermal dual-curable optical fiber bonding and fixing glue according to claim 1, characterized in that: The filler is any one or more of silicon powder, aluminum hydroxide, aluminum oxide, quartz powder, mica powder, kaolin and boron nitride.
10. A preparation method of the optical fiber bonding fixing glue according to any one of claims 1 to 9, comprising the following steps: Step one: the preparation of the base system, the weight parts of 20-60 parts of epoxy resin, 5-10 parts of diluent agent at room temperature for high speed dispersion, with 1200r / min speed stirring 30 minutes; Then continue to add filler 50-80 parts for dispersion, with 1200r / min speed stirring 30 minutes, then continue to add 0.5-3 parts of the rate of dispersion stirring 30 minutes, forming the optical fiber bonding fixed glue matrix; Step two: the addition of functional components, the addition of 1-10 parts of cationic initiator, the same weight of 1-10 parts of free radical photoinitiator, with 1000r / min speed stirring 30 minutes, forming a uniform and stable product optical fiber bonding fixed glue.
